A Study on Sb and F Doped Tin Oxide Thin Films Preparing in Condition of Different Temperature and Molarity and Their Physical Comparison - Duzgun, Bahattin; Battal, Ahmet (My University, 2019)
This article is about tin oxide (SnO2:Sb:F) thin films prepared (7 samples at each experiment step) successfully on the glass substrate by using spray pyrolysis method. Different solution molarities and different substrate temperatures were used to prepare precursor solution and fabricate thin films, respectively. And then these thin film’s structural, optical and morphological properties were compared. XRD patterns displayed that the deposited films were polycrystalline with tetragonal structure irrespective of molarity and substrate temperature. Each film has a transmittance of more than 60% in visible region. Optical band gap values were found to be in the range of 3.74-3.95 eV. The SEM and AFM images demonstrated that nanocrystalline particles covered all film surfaces. The best optimum property was found at thin films (0.15 M) prepared with at 520 ?C and the grains are larger for thin films at 520 ?C when compared with 480 ?C. Finally, it is understood that when substrate temperature and molarity increased, more regular structure was obtained.